Predictors of intraocular pressure change after cataract surgery in patients with pseudoexfoliation glaucoma and in nonglaucomatous patients - Markić Bojana; Mavija Milka; Smoljanović-Skočić Saša; Tepić-Popović Miljana; Burgić Sanela Sanja (Vojnosanitetski Pregled)
Background/Aim. The cataract surgery in eyes with and without glaucoma results in the sustained intraocular pressure (IOP) reduction but it is still unknown which glaucomatous patients will achieve clinically significant reduction. The preoperative IOP and some ocular biometric parameters have been shown as potential predictors of the postoperative IOP reduction. The aim of our prospective intervention study was to evaluate that relationship in medically controlled patients with the pseudoexfoliation glaucoma (PXG) and in the nonglaucomatous patients. Methods. Thirty-one PXG patients (31 eyes) and 31 nonglaucomatous patients (31 eyes), all with clinically significant cataract, were enrolled. The preoperative IOP, anterior chamber depth (ACD), axial length (AL), lens thickness (LT), lens position (LP) [LP = ACD + 0.5 LT], relative lens position (RLP) [RLP = LP / AL] and the pressure-to-depth ratio (PD ratio) [PD ratio = preoperative IOP/preoperative ACD] were evaluated as potential predictors of the IOP change in the 6th postoperative month. Results. In the 6th postoperative month, in the PXG group, the IOP reduction was -3.23 ± 3.41 mmHg (-17.67 ± 16.86%) from the preoperative value of 16.27 ± 3.08 mmHg and in the control group, the reduction was -2.26 ± 1.71 mmHg (-15.06 ± 10.93%) from the preoperative value of 14.53 ± 2.04 mmHg. In the PXG group, the significant predictors of the absolute and the percentage IOP reduction were the preoperative IOP, AL, and PD ratio. In the same group, RLP was shown as a significant predictor of absolute change in the IOP in multi-variate analysis, and the percentage IOP change in both the univariate and the multivariate analyses. In the control group, the preoperative IOP and the PD ratio were the only significant parameters that could predict absolute change in the postoperative IOP. Conclusion. The cataract surgery leads to the IOP reduction both in the PXG and nonglaucomatous eye. Predictors monitored in this study are widely available and simply calculable parameters that can be potentially used in managing glaucoma.